Stability of Variable-Number Tandem Repeats of Mycobacterial Interspersed Repetitive Units from 12 Loci in Serial Isolates of Mycobacterium tuberculosis - Savine, Evgueni (American Society for Microbiology (ASM), 2002)
Variable number tandem repeats (VNTRs) of elements named mycobacterial interspersed repetitive units (MIRUs) have previously been identified in 12 minisatellite loci of the Mycobacterium tuberculosis genome. These markers allow reliable high-throughput genotyping of M. tuberculosis and represent a portable approach to global molecular epidemiology of M. tuberculosis. To assess their temporal stability, we genotyped 123 serial isolates, separated by up to 6 years and belonging to a variety of distinct IS6110 restriction fragment length polymorphism (RFLP) families, from 56 patients who had positive sputum cultures. All 12 MIRU VNTR loci were completely identical within the groups of serial isolates in 55 out of 56 groups (98.2%), although 11 pairs of isolates from the same patients with conserved MIRU VNTRs displayed slightly different IS6110 RFLP profiles. In a single case, serial isolates with an unchanged IS6110 RFLP profile showed a change in 1 out of 12 MIRU VNTR loci. These results indicate that MIRU VNTRs are stable over time and therefore are suitable for reliable follow-up of patients chronically infected with tuberculosis over long periods. Moreover, they support MIRU VNTR genotyping as a powerful first-line method followed by subtyping by IS6110 RFLP to define ongoing transmission clusters.